El pensamiento de Sócrates / por A. E. Taylor ; [traducción de Mateo Hernández Barroso] - Taylor, A. E. (Alfred Edward) (Breviarios del Fondo de Cultura Económica; 161)
1° ed. 1961, reimp. de 1975 y 1985 | Bibliografía: p. 145-146. Índices